Merjenje odvisnosti relaksacijskih časov T spodaj 1 in T spodaj 2 od vlažnosti lesa - Stokelj, Eva (Matrika, 2017)
The subject of the article is usage of ?$^1H$? nuclear magnetic resonance for finding correlation between spin-lattice relaxation time ?$T_1$?, spin - spin relaxation time ?$T_2$? and moisture of wood. Different samples of wood were used for measurements. At first, ?$T_1$? and ?$T_2$? relaxation times were measured just for a beech tree sample. Later, another five samples of different types of wood were measured to see if there is any similarity between them. The experiment show that relaxation times ?$T_1$? are longer, relaxation times ?$T_2$? are shorter with lower moisture of wood and that there is difference in relaxation times between wood species.
Keywords: moisture of wood; relaksacijski časi; relaxation times; vlažnost lesa